ROLE OF AEROSOL PARTICLE IN THE TRANSMISSION OF INFLUENZA A VIRUS - Yuniadi Antari, Putu; Hendrayana, Made Agus (E-Jurnal Medika Udayana, 2013)
Normal 0 false false false EN-US X-NONE X-NONE Transmission of the Influenza A virus has been widely studied by scientists, as influenza states itself a disease capable of easily causing worldwide pandemic. Influenza pandemics are mediated by its virus, which holds the ability to undergo mutation in a vast speed. As a threatening nosocomial infection especially among patients with a high risk of contamination, influenza must be given serious attention. The objective of this article is to comprehend the effectiveness of aerosol particles in influenza transmission, as well as the role of health care centers in facilitating the spreading of this disease. Reviews in this article show that experimental animals demonstrate how aerosol particles do play a role in the transmission of the disease. In its relation with health care facilities, reviews show that different hospitals or clinics represent various numbers of aerosol particles necessary for causing clinical symptoms and signs of influenza in a group of patients. On the other hand, basic precaution instruments significantly reduce influenza transmission. In addition, this study also reviews a number of possible actions to prevent further transmission. Commitment and teamwork of involved stakeholders are necessary to ensure public awareness and initiate health promotions to eliminate any possibility of further pandemics. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: aerosol particle, Influenza A virus, health care facilities